PENGARUH POTONGAN HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI PELANGGAN DI PT. PLN UP3 BAUBAU (STUDI PADA PROGRAM “NYAMAN KOMPOR INDUKSI”) - Iqbal Nur, Muhammad; Hasni, Hasni; Zarliani Uli, Nur (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research aims to find out whether price discounts influence purchase interest, service quality influences purchase interest and whether price discounts and service quality simultaneously influence purchase interest at PT. PLN UP3 Baubau. This research uses a quantitative method. The population in this research is all customers of PT. PLN UP3 Baubau which uses the